Analysis for surface coke deposition in used Mo-Co/γ-Al2O3 catalyst for diesel hydrodesulfurization. (3rd July 2017) - Zhang, Qin; Zhao, Jigang; Guo, Rong; Sun, Jin; Shen, Benxian
ABSTRACT: The coked Mo-Co/γ-Al2 O3 catalysts were Soxhlet extracted with the solvent of tetrahydrofuran. Experimental techniques like FT-IR, GC-MS, XPS, H2 -TPR, BET, etc. were applied for the characterization of coke and catalysts to make a comparison of their physical properties. The results showed that the active components of the catalyst were slightly less after the reaction. The specific surface area and the pore volume had recovered to some degree. These results indicated that the main cause of deactivation of Mo-Co/γ-Al2 O3 catalysts is carbon deposit. The principal components of the soluble carbon deposit on Mo-Co/γ-Al2 O3 catalysts were alkyl aromatics with 1–4 rings and C19 –C29 long-chain alkane compounds.